(untitled) (Medicine Today, 2020)
Introduction: Down syndrome (DS) is the most common congenital abnormality affecting numerous organs and is associated with an increased incidence of many cutaneous diseases. Lichen Planus (LP) is a quite uncommon disease and associated with many immunologically altered condition. DS is also a medical condition with altered immune function. So, a higher research of LP associated with DS is very important for better understanding of both the diseases and also for comprehensive medical care. Case Report: A 33 years old known patient of Down Syndrome presented with signs and symptoms of LP is reported in this study. The diagnosis of LP was confirmed by histopathological study. She revealed a treatment history of several course of topical and systemic steroid since last 2 years for treatment of LP without any satisfactory outcome. After proper counseling we prescribed her systemic Acitretin (25 mg) daily for 3 months. She was examined every month for subsequent 3 months and was observed very satisfactory result. There was no relapse within one year after discontinuation of treatment. Discussion: We describe an adult patient with Down syndrome, associated with lichen planus (LP). LP is an inflammatory muco-cutaneous disease and benign in nature. However, some varieties of LP may cause considerable discomfort and need various systemic treatment. We treated the patient with systemic Retinoid with satisfactory result. Conclusion: LP associated with DS is a rare condition. It may be treated with systemic Retinoid. Medicine Today 2020 Vol.32(1): 70-72